W prześwitach poezji i filozofii, czyli tam, gdzie spotykają się Leśmian i Heidegger - Kłosowski, Mateusz (Przestrzenie Teorii, 2021)
The article presents the phenomenon of clearance in both the poetry of Bolesław Leśmian and the philosophy of Martin Heidegger. The author indicates the common points in both these thinkers’ investigations. In addition to a review of the previous discussions of this problem, the article postulates including the clearance in the group of aesthetic categories, because of its dynamic character. It also proposes a modified definition of clearance as a contrast of light with predominant albeit secondary darkness.